STUDI PEMIKIRAN HADIS DI INDONESIA Analisis Teori Hadis Hasbi Ash-Shiddieqy - Nadhiran, Hedhri (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-undangan, Ekonomi Islam, 2017)
This paper attempts to reveal the theory of Hadith of Ash- Shiddieqy, one of the reformers in Indonesia. This topic is interesting to be discussed because Hasbi has been known as an Islamic jurist so that his ideas in the field of Hadith development  are  almost  untouchable.  This  phenomenon strengthens the thesis of the Federspiel ? an Indonesianist, who  argues  that  the  study  of  hadith  is  particularly unpopular  in  Indonesia.  In  researching  Hasbi's  Hadith, the  focus  is  directed  to  three  crucial  issues  around  the polemic  of  modern  hadith  discourse,  which  is  about  the limits of the notion of hadith, hujjah and the science of fiqh al-hadis. The analysis of these three topics shows Hasbi's renewal  ideas  in  the  field  of  Hadith,  especially  in  the context  of  the  Indonesian  period.  This  at  once  shows  his independence for his ijtihad and does not want to be bound by bigotry against a particular school of thought.